PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBL) DALAM PEMBELAJARAN IPA MATERI EKOSISTEM DI MI MIFTAHUL ULUM 02 AJUNG JEMBER - La Tansa Michelia Champaka H.N; Muhammad Suwignyo Prayogo (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2024)
This study aims to describe the application of the Problem-Based Learning (PBL) model in learning Natural Sciences (IPA) ecosystem material in elementary schools. The research used a descriptive qualitative approach with observation, interview, and documentation techniques to collect data. The research subjects were teachers and grade V students at MI Miftahul Ulum 02 Ajung Jember. The results showed that the application of PBL in learning ecosystem material can help students actively participate, train critical thinking skills, and deepen students' concept understanding of ecosystems. However, some obstacles such as limited time and resources need to be considered in applying this model.